Diseño de una máquina automatizada para la perforación de tierra y posterior ubicación de la plántula de juglans neotrópica en llanuras (2017)
Starting from parameters and requirements necessary for the correct operation of the machine, three possibilities were analyzed for the machine and for the drilling element. Based on the approved functional design, the detailed design of the machine was made, the materials were selected according to the stresses in the mechanisms, followed by the analysis of the machine structure using a program of finite elements The manuals for the operation, assembly and maintenance of the machine were carried out, each with the basic recommendations and aspects to consider. The drawings of the mechanical elements, the pneumatic and electrical system of the machine were elaborated. Finally, the study of manufacturing and research costs for the production of the machine was carried out.